Measuring the dosage of brief and skill-targeted social-emotional learning (SEL) activities in humanitarian settings - Wu, Zezhen; Brown, Lindsay; Kim, Ha Yeon; Yoshikawa, Hirokazu; Aber, J. Lawrence (Frontiers in Psychology, 2023)
Introduction In humanitarian settings, social-emotional learning (SEL) programs for children are often delivered using a field-feasible approach where the programs are more easily deployable and adaptable in the field, require minimal training, and depend less on the strict sequence and structure of the program components to elicit the intended treatment effect. However, evidence is lacking on what aspects of this implementation approach enable the SEL programming to be more beneficial to children’s SEL development. Method In this study, we propose and evaluate measures for three dimensions of dosage (quantity, duration, and temporal pattern) of two sets of brief and skill-targeted SEL activities (Mindfulness and Brain Games) implemented in 20 primary schools in two low-income chiefdoms of Sierra Leone. Results We find preliminary evidence of predictive validity that these dosage measures could predict children’s attendance and classroom adaptive behavior. Discussion This study is the first to develop procedures to measure the dimensions of dosage of brief SEL activities in humanitarian settings. Our findings illuminate the need for future research on optimizing the dosage and implementation design of SEL programming using brief SEL activities.